Reforming Customs Clearance in Pakistan - Ahmad, Manzoor (World Bank, Washington, DC, 2012)
Simple, fast, transparent customs clearance procedures encourage trade-and the resulting tariffs and related taxes raise government revenue and stimulate economic development. After outsourcing failed to make customs more efficient or increase revenue, in 2002 Pakistan began pursuing a modern single window system for customs clearance. In 2005 the system was introduced at the port of Karachi, replacing numerous procedures with one electronic declaration and sharply cutting customs processing times. Despite dramatically reduced tariffs, annual customs revenue grew dramatically after the reform-though tariffs and customs reform have since stalled.